2009
DOI: 10.5021/ad.2009.21.3.237
|View full text |Cite
|
Sign up to set email alerts
|

A Global Gene Expression Analysis of the Peripheral Blood Mononuclear Cells Reveals the Gene Expression Signature in Psoriasis

Abstract: Background: Psoriasis is a chronic inflammatory skin disease that affects approximately 1~3% of the general population. Objective: We performed cDNA microarray analysis with using the dendrimer labelling method to investigate the gene expression profile in the peripheral blood mononuclear cells (PBMCs) of psoriatic patients. Methods: The peripheral blood mononuclear cells of 5 patients with psoriasis and 8 control subjects were used in the gene expression analyses of psoriasis. Results: We identified 212 diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
4
8
1
Order By: Relevance
“…The notion that low IL-7R expression levels are beneficial for reaching healthy old age corresponds with previous observations that patients suffering from autoimmune disease express increased levels of the IL-7 receptor/ligand complex genes [101, 102, 104] and that antagonizing IL-7 or the IL-7R may offer possible treatments [95, 101]. However, the results of the Leiden Longevity Study found that gene expression levels of IL-7R decrease with chronological age.…”
Section: Conclusion: the Yin And Yang Of Il-7 In Agingsupporting
confidence: 80%
“…The notion that low IL-7R expression levels are beneficial for reaching healthy old age corresponds with previous observations that patients suffering from autoimmune disease express increased levels of the IL-7 receptor/ligand complex genes [101, 102, 104] and that antagonizing IL-7 or the IL-7R may offer possible treatments [95, 101]. However, the results of the Leiden Longevity Study found that gene expression levels of IL-7R decrease with chronological age.…”
Section: Conclusion: the Yin And Yang Of Il-7 In Agingsupporting
confidence: 80%
“…This is similar to the major alterations in mRNA levels from psoriatic versus normal skin (Bowcock et al , 2001; Gudjonsson et al , 2010; Mee et al , 2007; Nomura et al , 2003; Quekenborn-Trinquet et al , 2005; Suarez-Farinas et al , 2010; Zhou et al , 2003). Psoriatic blood has limited expression changes compared to blood from healthy controls (Lee et al , 2009) and we would expect similar findings from an investigation of methylation alterations in this tissue…”
Section: Discussionsupporting
confidence: 56%
“…Since this theory conflicts with other findings [22,23,38], any association that may exist is likely to be weak and potentially restricted to specific populations. Down-expression of another cancer susceptibility gene, CDKN2A (predisposing to melanoma, cancers of the pancreas, breast and lung), led to speculation that the gene may have a role in the pathogenesis of psoriasis [24]. Our findings do not support this thesis.…”
Section: Discussioncontrasting
confidence: 80%
“…lead to tumour development. Some of these “cancer risk” gene alterations were also reported to be associated with psoriasis risk [22-24]. To evaluate the possible link between psoriasis and cancer, we examined the distribution of 17 mutations/polymorphisms in 10 known cancer susceptibility genes among patients and 517 matched healthy controls.…”
Section: Introductionmentioning
confidence: 99%